Development of a Model of Organizational Effectiveness Evaluation for Faculties of Education: An Application of Multilevel Causal Analysis - Makmee, Pattrawadee; Sujiva, Siridej; Kanjanawasee, Sirichai (Scholar: Human Sciences, 2015)
The objectives of the present research were (1) to develop an effective evaluation model for faculty of education of Higher Education in Thailand (2) to study causal factors at field level and department level for correlation and effect in effectiveness of faculty of education and (3) to test invariance of a multilevel causal analysis model of faculty of education effectiveness among public universities and public autonomous universities. The total of 913 samples were stratified randomly, and consisted of 33deans and administrators, 110 heads of field, 550 faculty members and 220 supporting staff in 4 public autonomous universities and 7 public universities in Thailand. Five-point Likert scales were used for the developed instruments with Cronbach‘s alphas ranging from 0.780 to 0.978. Statistical analyses were made based on descriptive statistics, Pearson‘s product moment correlation using SPSS version 16.0 for Windows. The multi-level confirmatory factor analysis and the multilevel causal model analysis were performed using Mplus version 5.21. The model of organizational effectiveness was described by nine variables namely, (1) educational satisfaction (2) academic development (3) faculty member‘s satisfaction (4) professional development (5) system openness and community interaction (6) ability to acquire resources and money (7) goal attainment (8) internal process management and (9) learning and development.